Colistin resistance in Escherichia coli confers protection of the cytoplasmic but not outer membrane from the polymyxin antibiotic. Issue 11 (1st November 2021) - Humphrey, Madeleine; Larrouy-Maumus, Gerald J.; Furniss, R. Christopher D.; Mavridou, Despoina A. I.; Sabnis, Akshay; Edwards, Andrew M.
Abstract : Colistin is a polymyxin antibiotic of last resort for the treatment of infections caused by multi-drug-resistant Gram-negative bacteria. By targeting lipopolysaccharide (LPS), the antibiotic disrupts both the outer and cytoplasmic membranes, leading to bacterial death and lysis. Colistin resistance in Escherichia coli occurs via mutations in the chromosome or the acquisition of mobilized colistin-resistance ( mcr ) genes. Both these colistin-resistance mechanisms result in chemical modifications to the LPS, with positively charged moieties added at the cytoplasmic membrane before the LPS is transported to the outer membrane. We have previously shown that MCR-1-mediated LPS modification protects the cytoplasmic but not the outer membrane from damage caused by colistin, enabling bacterial survival. However, it remains unclear whether this observation extends to colistin resistance conferred by other mcr genes, or resistance due to chromosomal mutations. Using a panel of clinical E. coli that had acquired mcr −1, –1.5, −2, –3, −3.2 or −5, or had acquired polymyxin resistance independently of mcr genes, we found that almost all isolates were susceptible to colistin-mediated permeabilization of the outer, but not cytoplasmic, membrane. Furthermore, we showed that permeabilization of the outer membrane of colistin-resistant isolates by the polymyxin is in turn sufficient to sensitize bacteria to the antibiotic rifampicin, which normally cannot cross the LPS monolayer. These findings demonstrate that colistin resistance in these E. coli isolates is due to protection of the cytoplasmic but not outer membrane from colistin-mediated damage, regardless of the mechanism of resistance.